Prevalence, Awareness, Treatment, and Control of Hypertension in China: Results From a National Survey - Wang, Jinwei; Zhang, Luxia; Wang, Fang; Liu, Lisheng; Wang, Haiyan (American journal of hypertension, 2014)
BACKGROUND Hypertension is one of the major risk factor for cardiovascular disease worldwide. The objective of this study was to investigate the prevalence, awareness, treatment, and control of hypertension in China. METHODS A multistage, stratified sampling method was used to obtain a representative sample of persons aged 18 years or older in the general population of China. Blood pressure (BP) was measured by sphygmomanometer 3 times at 5-minute intervals. Hypertension was defined as a systolic BP ≥ 140mm Hg, or diastolic BP ≥ 90mm Hg, or self-reported use of antihypertensive medications in the last 2 weeks irrespective of the BP. RESULTS Altogether 50,171 subjects finished the survey across the entire country. The adjusted prevalence of hypertension was 29.6% (95% confidence interval (CI) = 28.9%-30.4%) and was higher among men than among women (31.2%, 95% CI = 30.1%-32.4%; vs. 28.0%, 95% CI = 27.0%-29.0%). The awareness, treatment among all hypertensive participants, control among all hypertensive participants, and control among treated hypertensive participants were 42.6%, 34.1%, 9.3%, and 27.4%, respectively. Multiple lifestyle factors were independently associated with presence of hypertension, including physical inactivity, habitual drinking, chronic use of nonsteroidal anti-inflammatory drugs, high body mass index, and central obesity. CONCLUSIONS Hypertension is an important public health burden in China, and control of hypertension is still suboptimal. Several modifiable lifestyle activities were associated with hypertension and thus should be considered potential targets for intervention, with special attention to socioeconomically disadvantaged subpopulations in China.